Sonocatalytic degradation of fluoroquinolone compounds of levofloxacin using titanium and zirconium oxides nanostructures supported on paper sludge/wheat husk-derived biochar - Motlagh, Parisa Yekan; Soltani, Reza Darvishi Cheshmeh; Pesaran, Zoha; Akay, Sema; Kayan, Berkant; Yoon, Yeojoon; Khataee, Alireza (Elsevier Science Inc, 2022)
The present study aimed at treating a water medium containing pharmaceutical compounds such as levofloxacin (LEV). For this purpose, ultrasound (US)-based degradation of LEV was catalyzed by TiO2 and ZrO2 nano-catalysts supported on biochar (BC). BC was obtained from a precursor composite of paper sludge and wheat husk. The application of BC-ZrO2 led to a degradation efficiency of 54.65% within 60 min. When BC-TiO2 was used, a lower degradation efficiency of 49.62% was obtained at the same reaction time. However, increasing the time to 120 min improved the sonocatalytic degradation of LEV by BC-TiO2 (72.88%) compared to that of BC-ZrO2 (66.42%). In the presence of H2O2 and S2O82-, the LEV degradation efficiency of US/BC-TiO2 increased from 72.88% to 87.98% and 94.03%, respectively, and for the US/BC-ZrO2 process, it increased from 66.42% to 76.79% and 90.14%, respectively. The addition of isopropanol caused the most suppressive effect on the sonocatalytic degradation of LEV for both US/BC-TiO2 (decreasing from 72.88% to 13.99%) and US/BC-ZrO2 (decreasing from 66.42% to 16.43%) processes. The reusability test results showed an approximately 20% reduction in the sono-reactor performance within three consecutive experimental runs with no substantial change in the functional groups of the as-prepared sonocatalyst. Intermediates of LEV decomposed by the two sonocatalytic processes were also identified. (c) 2022 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Sonocatalysis; Catalyst; Biochar; Ultrasound; Nanoparticles; Advanced oxidation processes